2016
DOI: 10.1155/2016/6278709
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use as Risk or Protection for Type 2 Diabetes: A Longitudinal Study of 18 000 Swedish Men and Women

Abstract: Aims. Whether or not cannabis use may increase or decrease the risk of type 2 diabetes is not clear. We analyzed the association between cannabis and subsequent type 2 diabetes and if a potential positive or reverse association persisted after controlling for potential confounders. Methods. In this population-based cohort study, 17,967 Swedish men and women (aged 18–84 years), who answered an extensive questionnaire in 2002 (including questions on cannabis use), were followed up for new cases of type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
(42 reference statements)
1
38
1
3
Order By: Relevance
“…The percent of each group that consumed Cannabis was negatively and linearly related to the BMI of the group (R 2 = 0.96). Danielsson et al (Danielsson et al, 2016) also reported decreased rates of overweight (BMI > 24.9) in Cannabis users but did not provide numerical data for BMI of the two groups. Thus, of eleven studies reporting data on the relationship between Cannabis use and BMI, nine showed a significant negative relationship between Cannabis use and BMI while the remaining two either reported lower BMI values in Cannabis users than non-users that did not reach statistical significance, or failed to provide statistical analyses (Table 1).…”
Section: Results: Bmi Datamentioning
confidence: 96%
See 3 more Smart Citations
“…The percent of each group that consumed Cannabis was negatively and linearly related to the BMI of the group (R 2 = 0.96). Danielsson et al (Danielsson et al, 2016) also reported decreased rates of overweight (BMI > 24.9) in Cannabis users but did not provide numerical data for BMI of the two groups. Thus, of eleven studies reporting data on the relationship between Cannabis use and BMI, nine showed a significant negative relationship between Cannabis use and BMI while the remaining two either reported lower BMI values in Cannabis users than non-users that did not reach statistical significance, or failed to provide statistical analyses (Table 1).…”
Section: Results: Bmi Datamentioning
confidence: 96%
“…In contrast, analysis of data from the CARDIA data set failed to detect this relationship (Bancks et al, 2015). Daniellson et al (Danielsson et al, 2016) found decreased rates of DM in Cannabis users in a dataset of Swedish conscripts (OR 0.74), but unlike the studies from the NHANES data set this effect was no longer significant after adjustment for age (AOR 0.74 prior to adjustment, 0.94 after adjustment).…”
Section: Observations Supporting This Theorymentioning
confidence: 92%
See 2 more Smart Citations
“…A greater risk for prediabetes (hazard ratio [HR], 1.39 [95% CI, 1.13 to 1.71]) was identified among participants who reported using marijuana 100 or more times during follow-up compared with nonusers. The final prospective study (high ROB) followed 18 000 Swedish men and women aged 18 to 84 years over 10 years but assessed marijuana exposure only once, at baseline (27). Measures of socioeconomic factors, diet, or other drug use at baseline were limited.…”
Section: Resultsmentioning
confidence: 99%